Makna Tindakan Pragmatik Bedhaya Tejaningsih pada Jumenengan K.G.P.H Tejawulan Sebagai Raja Paku Buwana XIII di Surakarta - Maryono, Maryono (PANGGUNG, 2017)
AbstractThe presence of Bedhaya Tejaningsih in the inauguration or jumenengan ritual of K.G.P.H Tejawulan is evidently not only a form of entertainment but also contains a symbolic meaning. In this pragmatic study of Bedhaya Tejaningsih, the writer uses a pragmatic linguistic approach. The research is qualitative interpretative in nature and uses as a basic reference pragmatic theories and performing art theories. The methods used for collecting data include a library study, observation, and interviews. The results of the study show that the meaning of the presence of the dance Bedhaya Tejaningsih in the jumenengan ritual of K.G.P.H Tejawulan is a form of entertainment, exemplification, and credibility. As a form of entertainment, the presence of the dance Bedhaya Tejaningsih at the king coronation provides an aesthetical presentation for the audience. The meaning of its exemplification is seen in the request it makes to the general public to follow the example of a good and wise leader who always prioritizes his love for the people in the way he provides them with protection, peace, and security. The meaning of credibility is K.G.P.H Tejawulan is request that the people will give their support and recognition of his inauguration to become king so that he gains legitimacy based on the cultural tradition of the Kasunanan Palace in Surakarta.Keywords: Bedhaya Tejaningsih dance, meaning of pragmatic action, and jumenengan.AbstrakKehadiran Bedhaya Tejaningsih pada ritual jumenengan K.G.P.H Tejawulan rupanya tidak sekadar bentuk hiburan, namun mengandung makna simbolis. Pada Penelitian pragmatik Bedhaya Tejaningsih, peneliti menggunakan pendekatan linguistik pragmatik. Bentuk penelitiannya bersifat kualitatif interpretatif dengan dasar rujukan teori-teori pragmatik dan seni pertunjukan. Metode pengumpulan datanya dengan cara: studi pustaka, observasi dan wawancara. Hasil kajian menunjukkan bahwa makna kehadiran tari Bedhaya Tejaningsih pada ritual jumenengan K.G.P.H Tejawulan merupakan bentuk hiburan, keteladanan dan kredibilitas. Sebagai bentuk hiburan kehadiran tari Bedhaya Tejaningsih pada penobatan raja secara keseluruhan sajiannya memberikan santapan estetis bagi penonton. Makna keteladanan yang ditemukan adalah bentuk permintaan terhadap masyarakat untuk meneladani figur pemimpin yang baik dan bijak yang selalu mengutamakan cinta kasih dalam mengayomi masyarakat, menciptakan ketentraman dan kedamaian. Makna kredibilitas adalah permohonan K.G.P.H Tejawulan terhadap masyarakat untuk memberi dukungan dan pengakuan atas penobatannya sebagai raja supaya memiliki legitimasi berdasar adat budaya Karaton Kasunanan Surakarta.Kata kunci: tari Bedhaya Tejaningsih, makna tindakan pragmatik, dan jumenengan.Â